Analisis Dampak Media Sosial terhadap Minat Wisata Inbound: Studi Kasus Instagram @jaswitatourism di Jawa Barat - Ibrahim, Airin Rahmanu; Sukirman, Oman; Asy'ari, Rifqi (Pusat Studi Pariwisata Universitas Gadjah Mada, 2025)
The @jaswitatourism account is a digital promotional platform managed by PT Jaswita Jabar (Perseroda), a state-owned enterprise (BUMD) operating in the services and tourism sector. Social media is considered effective in shaping perceptions, destination imagery, and tourist interest. This study employs a quantitative approach using descriptive and correlational methods. Data was collected through a questionnaire distributed to 97 respondents. Since the data was not normally distributed, the Spearman Rank test and Rank-Based Regression were used to test the hypotheses. The results indicate that social media has a significant influence on inbound tourism interest, with a determination coefficient of 65.3%. This means that social media explains more than half of the variation in respondents' tourism interest. Descriptive results also show that most indicators scored high, particularly in content creation and destination image, although there are still weaknesses in content sharing.